EFFECT COSE AND MCSQ ON SERVICE RECOVERY AND ITS IMPACT ON CUSTOMER SATISFACTION HOSPITAL DR. ISKAK TULUNGAGUNG (Studies in Outpatient) (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study Aimed to describe MCSQ, COSE, service recovery and customer satisfaction Hospital Dr. Iskak Tulungagung; COSE MCSQ and analyze the effect on service recovery; COSE MCSQ and analyze the effect on customer satisfaction; analyze the influence of service recovery on customer satisfaction, and analyze the effect MCSQ and COSE to customer satisfaction through service recovery Hospital Dr. Iskak Tulungagung. The analysis technique used deskritpif analysis and structural equation modeling. The analysis Showed that MCSQ is formed by supportive management and investment in technology. COSE in this case the patient formed by the technical skills, social skills, motivation and decision making authority, Service recovery is formed of a responsive and compensation. Customer satisfaction is formed of patient services that meet expectations, the impression in receiving care and experience for services received. MCSQ and COSE effect on service recovery. MCSQ and COSE effect on customer satisfaction. Service recovery effect on customer satisfaction. Service recovery, MCSQ and COSE are mediating the influence on customer satisfaction.